OP40 #Association between supermarket checkout food policies and purchases of common less healthy checkout foods: interrupted time series analyses and meta-analysis of natural experiments. (September 2018) - Ejlerskov, KR; Stead, M; Adamson, AJ; White, M; Adams, J
Abstract : Background: Supermarkets' in-store marketing influences food purchasing and consumption. This marketing includes positioning food at checkouts. Checkouts provide a unique location, through which all customers must pass and where some may linger. The majority of supermarket checkout food is less healthy. Supermarket activities with potential to improve population health are increasing. One example is voluntary, supermarket-led policies on checkout foods. We studied the immediate and sustained impacts of the introduction of voluntary, supermarket-led checkout food policies on purchases of commonly displayed checkout foods. Methods: Eight national supermarket groups were included. Intervention groups were those that changed their checkout food policy between January 2014 and February 2016 (n=6). Supermarket group-specific data on purchases of common checkout foods was obtained from Kantar Worldpanel's 'Take Home' panel: a representative panel of UK households (n≈30, 000) who record all food and beverage purchases brought into the home. We obtained data at the four-weekly level, multiplied up and weighted by Kantar to represent the total UK market. Kantar also provided supermarket group market share data. Common checkout foods, selected based on a previous survey, were: single-unit packages of sugary confectionery (≤225 g), chocolate (≤125 g), and crisps (≤50 g). Controlled interrupted time-series analyses were conducted of changes in purchases of common supermarket checkout foods in the 14 four-weekly periods before, and the 13 four-weekly periods after, implementation of checkout food policies – in units purchased per percentage market share. As different supermarket groups implemented policies at different times, separate analyses were conducted for each group. Supermarket groups that did not change their policies during the study period were used as comparators (n=2). Results were synthesised using random-effects meta-analyses. Data analyses were conducted in Stata/SE v14.2 and R v3.3.1. Results: In meta-analyses, implementation of supermarket checkout food policies was associated with a statistically significant decrease in purchases of common checkout foods of 1 37 160 units per percentage market share in the four weeks following policy implementation (95% confidence intervals (CI): −252, 690 to −21, 630). By 12 months this effect had diminished (−57, 080; 95% CI −167, 760 to 53, 590). Conclusion: Implementation of supermarket checkout food policies was associated with an immediate reduction in purchases of sugary confectionery, chocolate and crisps that was not sustained at one year. Voluntary supermarket-led activities have the potential to decrease purchases of less healthy foods. Initial effects may be undermined over time by changes in behaviour of supermarkets, consumers, or both. The data are observational and exclude purchases not brought home.